A Development of a Financial Literacy Pocket Book for Malay Tribe Housewives in Running a Home Industry Business - Mayasari, Mayasari; Putri, Rumanintya Lisaria; Harsono, Iwan; Wahyono, Eko; Prayoga, Reza Amarta; Sutrisno, Joko; Suprapto, Suprapto; Ristyana, Rida (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
This study aims to identify the need for developing a financial literacy pocketbook for Malay ethnic homemakers in running a home industry business, compiling a financial literacy pocket bookmaking tool, and measuring or knowing the validation of the financial literacy pocketbook. This study uses a design-based research (DBR) approach. The subjects in this study were 25 Malay homemakers running a home industry business in Jambi City. For the implementation of field trials (in large groups) and evaluation of field trials, the researchers used action research to test the draft financial literacy pocketbook product. Researchers collected data using the method of observation, in-depth interviews, questionnaires, FGD (focus group discussion), and documentation. The data analysis used by researchers in processing research and development data used qualitative and quantitative analysis. The results of the field test showed that before the pre-test comprehension treatment was conducted, it was 57.71, while after the treatment of understanding financial literacy using a literacy pocketbook, it was known that the average result of understanding Jambi Malay homemakers about financial literacy with a post-test was 67.02 which means an increase of 9.31 points. The effect size calculation results show a value of 0.861, which is included in the high category. Overall, this study has produced a pocketbook of home industry financial literacy measuring 7 x 10 cm with 25 pages of teaching materials that professionals have validated.